A study of hepatobiliary manifestations in dengue viral infection - N., Venkata Rajaih; Thirunadhar, R.; Dasari, Nikitha (International Journal of Advances in Medicine, 2019)
Background: Dengue viral infection is a major and important public health problem in many South East Asian (SEA) countries and also in more than 100 countries of tropical and subtropical region. The aim of study was to assess the frequency and degree of hepatobiliary dysfunction in adults with dengue infection presenting to our tertiary hospital, Karimnagar. Methods: The study was a prospective observational study conducted on 120 adult patients of serological proven dengue infection with hepatic and biliary manifestations, admitted during the period of from June 2016 to June 2017. Investigations included complete blood count, liver function test, viral serology, sepsis screen, ultrasound abdomen. Results: Majority of cases in age group of 20-56 years with male: female ration of 1.7:1. Of all the cases, 53% patients were categorized into dengue fever group, 25% into dengue hemorrhagic fever group, and 27.7% into dengue shock syndrome group in accordance to WHO guidelines. Conclusions: This study was showed that a significant hepatobiliary derangement is seen in severe cases of dengue. Early recognition of such perturbations helps guide further management to prevent mortality.